Weighted Product and Its Application to Measure Employee Performance - Aminudin, Nur; Sundari, Eni; K, Shankar; Deepalakshmi, P; ., Fauzi; Irviani, Rita; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
The decision support system of employee performance index appraisal is a decision support system that can assist decision makers for employee performance appraisal at the Pringsewu district revenue department. As for the purpose of this DSS namely 1. To make decisions in the field of human resources to come, 2. To evaluate the performance of each employee in achieving the target work that has been determined , 3. For improve employee performance in the future. The problems to be solved are: 1. How to change the assessment process that used to still use manual way by computerization. 2. How to apply the progress of change in today's sophisticated technology. In this decision system using Weighted Product (WP) weighting method of WP method is the choice of method on decision support system of employee performance appraisal index at revenue department of Pringsewu district. Weighted product method is a method of completion by using multiplication to attribute attribute rating in which rating must be prefixed with bob ot attribute in question. This decision support system can perform the process of calculating employee performance appraisal so that it can realize a fair assessment based on existing criteria calculations on this system using weighted product weighting (WP) that can produce the best employee performance appraisal system calculation from the highest value of 0.250 to the lowest value of 0.133 . The highest score is the best employee while the lowest score is the worst employee performance. This system can present employee performance appraisal reports quickly and clearly so that more effective and efficient.Â Â